Design of a Two-Point Temperature Monitoring System on a Heating Medium Based on Arduino Mega 2560 and IoT - Nataly Wisnu Anggara; Mario Gracio Anduinta Rhizma (Universitas Pelita Harapan, 2026)
This research aims to design a two-point temperature monitoring system using 2 DS18B20 sensors on a heating medium using DS18B20 sensors controlled by an Arduino Mega 2560 and integrated with Internet of Things (IoT) technology. The measured data are processed by the microcontroller and transmitted via the ESP8266 module to the Firebase platform, then displayed on a smartphone application and recorded as historical data. The experimental results show that the DS18B20 sensors are able to read temperature changes linearly within the tested temperature range of approximately 27°C to 67°C and can follow the temperature increase trend of the heating medium. To improve measurement accuracy, calibration was performed using a linear regression method with a surface thermocouple as the reference instrument. After calibration, the measurement error was significantly reduced to 2.90% at the upper measurement point and 2.66% at the lower measurement point, indicating that the system is more representative for monitoring temperature changes at two measurement locations. The proposed demonstrates decent performance as an IoT-based temperature monitoring prototype, making it suitable for small-scale heating applications and educational purposes.